2010
DOI: 10.1371/journal.pone.0009611
|View full text |Cite|
|
Sign up to set email alerts
|

Reactivation of Latent Tuberculosis in Cynomolgus Macaques Infected with SIV Is Associated with Early Peripheral T Cell Depletion and Not Virus Load

Abstract: HIV-infected individuals with latent Mycobacterium tuberculosis (Mtb) infection are at significantly greater risk of reactivation tuberculosis (TB) than HIV-negative individuals with latent TB, even while CD4 T cell numbers are well preserved. Factors underlying high rates of reactivation are poorly understood and investigative tools are limited. We used cynomolgus macaques with latent TB co-infected with SIVmac251 to develop the first animal model of reactivated TB in HIV-infected humans to better explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 43 publications
8
191
0
Order By: Relevance
“…Macaques serve as excellent models of human Mtb/HIV coinfection because they can establish LTBI and are susceptible to simian immunodeficiency virus (SIV), providing a valuable surrogate model for pathogenic HIV infection (22)(23)(24)(25)(26). Coinfected macaques recapitulate key aspects of the human disease, including CD4 + T-cell depletion, reactivation of LTBI, and dissemination of the bacilli (22,25).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Macaques serve as excellent models of human Mtb/HIV coinfection because they can establish LTBI and are susceptible to simian immunodeficiency virus (SIV), providing a valuable surrogate model for pathogenic HIV infection (22)(23)(24)(25)(26). Coinfected macaques recapitulate key aspects of the human disease, including CD4 + T-cell depletion, reactivation of LTBI, and dissemination of the bacilli (22,25).…”
Section: Significancementioning
confidence: 99%
“…Coinfected macaques recapitulate key aspects of the human disease, including CD4 + T-cell depletion, reactivation of LTBI, and dissemination of the bacilli (22,25). As part of the current investigation, we sought to understand the dynamics of TB disease progression following high-dose SIV coinfection in rhesus macaques and to establish the correlates associated with reactivation of LTBI.…”
Section: Significancementioning
confidence: 99%
“…At necropsy, we obtained numerous samples from granulomas, lung lobes, thoracic lymph nodes, and extrapulmonary sites and used quantitative tools we developed and described in detail previously to score gross pathology, bacterial burden, and dissemination (19). These scoring systems distinguish clinically defined active, latent, and reactivated TB in macaques (19,21). The outbred nature of macaques introduces substantial variability among animals in terms of disease progression and response to therapies, just as in humans, which makes this a challenging but realistic model for testing therapeutics.…”
Section: Short-course Mtz or Inh/rif Is As Effective As 6 Mo Inh In Pmentioning
confidence: 99%
“…Lawn et al showed that the HIV-infected individuals with fewer peripheral CD4 + T cells are more prone to TB than HIV-infected individuals with relatively higher CD4 + T cells [10]. Furthermore, the study of Diedrich et al reported that the reactivation of latent M. tuberculosis in cynomolgus macaques infected with simian immunodeficiency virus (SIV) is associated with early peripheral T cell depletion even before the rise in SIV viral load [11].…”
Section: Quantitative Changesmentioning
confidence: 99%